Evaluation of highly sensitive diagnostic tools for the detection of P. falciparum in pregnant women attending antenatal care visits in Colombia (2020)
ABSTRACT: Background: In low transmission settings early diagnosis is the main strategy to reduce adverse outcomes of malaria in pregnancy; however, microscopy and rapid diagnostic tests (RDTs) are inadequate for detecting low-density infections. We studied the performance of the highly sensitive-RDT (hsRDT) and the loop mediated isothermal DNA amplification (LAMP) for the detection of P. falciparum in pregnant women. Methods: A cross-sectional study was conducted in two malaria-endemic municipalities in Colombia. We screened pregnant women in the context of an antenatal care program in health facilities and evaluated five tests (microscopy, conventional RDT, hsRDT, LAMP and nested polymerase chain reaction-PCR) for the detection of P. falciparum in peripheral blood, using a quantitative reverse transcription PCR (qRT-PCR) as the reference standard. Diagnostic performance of hsRDT and LAMP were compared with routine testing. Results: The prevalence of P. falciparum was 4.5% by qRT-PCR, half of those infections were subpatent. The sensitivity of the hsRDT (64.1%) was slightly better compared to microscopy and cRDT (59 and 53.8% respectively). LAMP had the highest sensitivity (89.7%) for detecting P. falciparum and the ability to detect very low-density infections (minimum parasite density detected 0.08 p/μL). Conclusions: There is an underestimation of Plasmodium spp. infections by tests routinely used in pregnant women attending antenatal care visits. LAMP methodology can be successfully implemented at local hospitals in malaria-endemic areas. The relevance of detecting and treating this sub-patent P. falciparum infections in pregnant women should be evaluated. Trial registration: ClinicalTrials.gov, Identifier: NCT03172221 , Date of registration: May 29, 2017. Keywords: Diagnostics; Loop mediated isothermal DNA amplification (LAMP); Malaria in pregnancy; Microscopy; Nucleic acid amplification techniques; Rapid diagnostic test.